Confirming the Receipts of International Tourism in Indonesia after the COVID-19 Pandemic: Analyzed with Macroeconomic Indicators - Asma Munifatussaidah; Jihan Nabila Zahara; Siti Zubaidah (Universitas Airlangga, 2023)
This study aims to analyze International Tourism Receipts in Indonesia with the variables of International Trade, Inflation, and Exchange Rates during and after the COVID-19 pandemic. The analysis technique used to answer the problem is regression analysis using the Ordinary Least Squares (OLS) method. This type of research data uses secondary data obtained from the World Bank, Central Statistics Agency, and Bank Indonesia during the 2002-2022 period. The results of research analysis show that 1) the International Trade variable has a significant negative effect on International Tourism Receipts in Indonesia during and after the COVID-19 pandemic. The stability of international trade fluctuates, tends to decrease, but after the COVID-19 pandemic and the relaxation of social distancing policies, there has been an increase in international tourism. 2) The Inflation variable has a significant negative effect on International Tourism Receipts in Indonesia. A higher inflation rate increases living and travel costs, then reduces tourist interest. 3) The exchange rate variable has a significant and positive effect toward international tourism receipts. The increase of dollar exchange rate against the rupiah, will increase tourist interest in Indonesia. The implications of the results of this research are important for stakeholders and tourism sector companies so that they can continuously increase International Tourism Receipts in Indonesia through keeping macroeconomic indicators consisting of International Trade, Inflation and Exchange in Indonesia.